442 Feasibility of a Sleep Technologist Driven Intervention Protocol to Address CPAP Adherence in Hospitalized Patients. (3rd May 2021) - Cheng, Shan; Rivera, Elizabeth; Beauchamp, William; Cabral, Laiheng; Calero, Karel; Nallu, Sagarika; Holderman, Deborah; Schoonover, Doris; Johnson, Linda; Anderson, William
Abstract: Introduction: Obstructive sleep apnea (OSA) is associated with development of high blood pressure, diabetes, pulmonary hypertension, heart attack, stroke, atrial fibrillation, motor vehicle accidents, and death. These comorbidities may result in hospital admissions. Much of the therapy has been directed towards outpatient treatment with CPAP. Unfortunately, patient adherence to CPAP therapy is not optimal. We conducted a feasibility study to determine if a sleep technologist driven intervention protocol could address CPAP adherence in hospitalized patients. Methods: Tampa General Hospital Sleep Center developed a quality improvement protocol that would address inadequate CPAP adherence. The components include: 1. Education on the cause and need for treatment of OSA based on comorbidities, 2. Choosing a patient preferred mask, 3. Mask desensitization while awake. These criteria were used to test the feasibility of implementing this protocol in hospitalized patients: 1. Completion of the protocol within 48 hours of receiving a consult, 2. Implementation of various components of the protocol, 3. Obtaining outcome measures to evaluate efficacy. Outcome measures include patient willingness to retry CPAP (on a scale from 0–10) and CPAP smartcard download. Additional outcome data included: patient reasoning for CPAP noncompliance and self-administered questionnaires (ESS, ISI, GAD-7, PHQ-9, SF-26). Results: During November 2020, 31 inpatient consults were placed to the TGH Sleep Center. Within 48 hours of consult, the technologists implemented the protocol in 19 patients – 17 received mask fittings, 3 received education, and 3 had CPAP setting adjustments. 9 patients indicated their willingness to retry CPAP with an average rating of 9.1. 7 compliance downloads were obtained the following morning and usage ranged from 0:52 to 11:07 hours. 12 consults were not completed due to not meeting inclusion criteria (5), patient refusal (4), or other reasons (3). Conclusion: This study demonstrates feasibility of a sleep technologist driven intervention protocol to address CPAP adherence in hospitalized patients. However, there were inconsistencies in protocol execution and obtaining outcome measures. We speculate that protocol improvement will require: 1. More consistent patient education, 2. Better correction of patient specific adherence issues, 3. Obtaining all smartcard downloads, 4. Compiling outcome measures using a convenient digital interface. Support (if any):